2018
DOI: 10.1002/2017gl075976
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Inherited Fractures in the Critical Zone Using Seismic Anisotropy From Circular Surveys

Abstract: Weathering and hydrological processes in Earth's shallow subsurface are influenced by inherited bedrock structures, such as bedding planes, faults, joints, and fractures. However, these structures are difficult to observe in soil‐mantled landscapes. Steeply dipping structures with a dominant orientation are detectable by seismic anisotropy, with fast wave speeds along the strike of structures. We measured shallow (~2–4 m) seismic anisotropy using “circle shots,” geophones deployed in a circle around a central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 47 publications
6
58
0
Order By: Relevance
“…This is consistent with a large depression in the seismic surface (Fig. 8a) and has a strike consistent with the fast direction identified through seismic anisotropy (Novitsky et al, 2018) and the outcrop to the northeast (Fig. 1b).…”
Section: Insights About the Saprolite–fractured Bedrock Boundarysupporting
confidence: 88%
See 3 more Smart Citations
“…This is consistent with a large depression in the seismic surface (Fig. 8a) and has a strike consistent with the fast direction identified through seismic anisotropy (Novitsky et al, 2018) and the outcrop to the northeast (Fig. 1b).…”
Section: Insights About the Saprolite–fractured Bedrock Boundarysupporting
confidence: 88%
“…Outcrop is limited within our study area, but outcrops ∼1 km northeast of the study show a clear fracture orientation that has a strike of approximately 50° (Fig. 1b; Novitsky et al, 2018). Underneath the ridge at our study site, the water table is between 12 and 13 m below the ground surface (Flinchum et al, 2018a).…”
Section: Site Descriptionmentioning
confidence: 79%
See 2 more Smart Citations
“…We interpret this feature as a remnant fracture of the parent bedrock material contained within the weathered saprolite. Recent work by Novitsky et al () showed that remnant fractures such as these are common within this watershed and are predominantly aligned with the NE–SW fracture direction of Sherman granite outcrops distributed across the area. At relatively shallow depths (~2.5 to 6 m), fractured bedrock is reached and persists well beneath our area of investigation.…”
Section: Discussionmentioning
confidence: 99%